Analysis of Early Reading Difficulties in Second Grade Elementary School Students - Fatonah, Nurul; Damaianti, Vismaia S; Syaodih, Ernawulan (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
This research aims to analyze the early reading difficulties of second-grade elementary school students using the EGRA (Early Grade Reading Assessment) test. The research method used is a descriptive qualitative approach involving 20 second-grade students from several elementary schools. The instrument is based on the EGRA test as a measure to identify the level of early reading ability of students. The results show students' difficulties in early reading, including letter recognition, reading text recognition, word comprehension problems, and reading fluency. Data analysis also shows differences in reading ability levels among students, with most facing challenges in accurately identifying and understanding words. The implications of this research emphasize the need for developing appropriate teaching strategies to help students overcome their reading difficulties. This study is expected to contribute to developing more effective early literacy programs and support students' progress in reading at the primary education level.